Digital Activism and Political Change: Challenges of Social Media's Impact on Political Development - Rachimoellah, Muhammad; Lubis, Putri Handayani; Utimadini, Nindya Juwita (Journal Of Middle East and Islamic Studies, 2024)
This research investigates the influence of social media on political change and the role of digital activism, with a particular emphasis on the obstacles of disinformation and polarism. The employed approach is a qualitative research examining literature pertinent to network society, political participation, and collective action theories. The findings indicate that social media enhances and broadens political mobilization by reducing participation barriers, enabling individuals to engage in political activity more inclusively. Nonetheless, obstacles such as political polarization and the proliferation of disinformation pose substantial impediments to the efficacy of digital engagement. In Indonesia, the polarization problem is intensified by using social media in political campaigns and social movements, with echo chambers and filter bubbles amplifying ideological distinctions. Moreover, pervasive disinformation disseminated via platforms like Facebook, WhatsApp, and Twitter frequently distorts public sentiment and erodes political movements' legitimacy. In conclusion, although social media possesses significant potential to enhance political engagement and organize the populace, the obstacles presented by polarization and disinformation impede the enduring efficacy of political transformation instigated by digital activism. Consequently, enhanced digital literacy and more stringent laws are essential to tackle these challenges and ensure that social media is a potent instrument for fortifying democracy.